Proton Affinity in the Chemistry of Beta-Octamolybdate: HPLC-ICP-AES, NMR and Structural Studies - Victoria V. Volchek; Nikolay B. Kompankov; Maxim N. Sokolov; Pavel A. Abramov (Molecules, 2022)
The affinity of [β-Mo8O26]4− toward different proton sources has been studied in various conditions. The proposed sites for proton coordination were highlighted with single crystal X-ray diffraction (SCXRD) analysis of (Bu4N)3[β-{Ag(py-NH2)Mo8O26]}] (1) and from analysis of reported structures. Structural rearrangement of [β-Mo8O26]4− as a direct response to protonation was studied in solution with 95Mo NMR and HPLC-ICP-AES techniques. A new type of proton transfer reaction between (Bu4N)4[β-Mo8O26] and (Bu4N)4H2[V10O28] in DMSO results in both polyoxometalates transformation into [V2Mo4O19]4−, which was confirmed by the 95Mo, 51V NMR and HPLC-ICP-AES techniques. The same type of reaction with [H4SiW12O40] in DMSO leads to metal redistribution with formation of [W2Mo4O19]2−.